The 2009 Claremont Debates-Appendix A: David Fetterman's PowerPoint Slides - David M. Fetterman (The Evaluation Center at Western Michigan University, 2010)
Dr. David Fetterman's slide deck from the 2009 Claremont Evaluation Debates.